Analisis Persepsi, Sikap dan Preferensi Terhadap Kepuasan Konsumen pada UMKM Makanan Ringan - Dinda Amalia; Erni Yuningsih; Endang Silaningsih (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The decline in the number of UMKM in Sukabumi City is inseparable from the lack of independence of business actors in production process technology, weak financial management, and incompetent human resources are problems that are often faced by UMKM business actors in Sukabumi City. This study aims to analyze the influence of variables of perception, attitude and consumer preference on customer satisfaction. The research method used was probability sampling using a questionnaire as an instrument to collect data from 100 respondents. The results of this study indicate that simultaneously, perceptions, attitudes and consumer preferences have a positive and significant effect on customer satisfaction, with an R Square value of 61.1%. The remaining 38.9% is influenced by other factors not examined in this study. Perceptions, attitudes and preferences also have a significant effect on customer satisfaction. The results showed that consumer preference variables had a greater influence than perception and attitude variables on customer satisfaction of Snack Food UMKM in Sukabumi City. The conclusion is that in the context of Snack Food UMKM in Sukabumi City, both perceptions, attitudes and preferences are essential factors that need to be considered in determining customer satisfaction.